THE SPECIFIC FEATURES OF HEART AND VESSELS REMODELING IN PATIENTS WITH CHRONIC HEART FAILURE TREATED WITH LISINOPRIL DURING 6 MONTHS - N. A. Kosheleva; A. P. Rebrov (Рациональная фармакотерапия в кардиологии, 2016)
Background. Being able to attenuate pathological remodeling, ACE inhibitors are considered to be first line medications for chronic heart failure (CHF) treatment.Aim. To study the influence of the 6-month combined therapy with lisinopril on the heart and vessels remodeling in patients with ischemic CHF.Material and Methods. 40 patients with CHF after Q-myocardial infarction were treated with lisinopril (Listril, Dr.Reddy’s, India) as a part of complex therapy. Initially and after 6 months of therapy the following findings were evaluated: the 6-minute walk test results, echocardiography parameters, main arteries rigidity, endothelium-dependent and independent vasodilatation, anticoagulant and fibrinolytic function of vascular endothelium, von Willebrand factor (VWF).Results. 6-month treatment with lisinopril showed reduction in CHF functional class in 30 % of patients and increase in left ventricle (LV) stroke volume by 3,8% and LV ejection fraction by 1%. Pulse-wave velocity reduced insignificantly from 10,2 to 9,2 m/sec and augmentation indices of aorta from 31,4% to 29,9% as well as this of brachial artery from -2,6% to -6%. Endothelium-dependent vasodilatation increased from 6,4% to 8,6% and independent vasodilatation – from 13,8% to 16,6%. VWF activity decrease was observed in 40% of CHF patients. Significant changes in anticoagulant and fibrinolytic function of vascular endothelium were not revealed.Conclusion. Lisinopril administration as a part of complex therapy of CHF patients during 6 months resulted in favorable effect on heart and vessels remodeling and was well tolerated.